Estrogen receptor β activation alleviates inflammatory bowel disease by suppressing NLRP3-dependent IL-1β production in macrophages via downregulation of intracellular calcium level - Yanrong Zhu; Yilei Guo; Pengxiang Guo; Jing Zhang; Yue He; Yufeng Xia; Zhifeng Wei; Yue Dai (Journal of Advanced Research)
Introduction: Although several estrogen receptor β (ERβ) agonists have been reported to alleviate IBD, the pivotal mechanism remains obscure. Objectives: To examine the effects and mechanisms of ERβ activation on cytokine/chemokine networks in colitis mice. Methods: Dextran sulfate sodium salt (DSS) and trinitro-benzene-sulfonic acid (TNBS) were used to induce mouse colitis model. Multiple molecular biological methods were employed to evaluate the severity of mouse colitis and the level of cytokine and/or chemokine. Results: Bioinformatics analysis, ELISA and immunofluorescence results showed that the targeted cytokines and/or chemokines associated with ERβ expression and activation is IL-1β, and the anti-colitis effect of ERβ activation was significantly attenuated by the overexpression of AAV9-IL-1β. Immunofluorescence analysis indicated that ERβ activation led to most evident downregulation of IL-1β expression in colonic macrophages as compared to monocytes and neutrophils. Given the pivotal roles of NLRP3, NLRC4, and AIM2 inflammasome activation in the production of IL-1β, we examined the influence of ERβ activation on inflammasome activity. ELISA and WB results showed that ERβ activation selectively blocked the NLRP3 inflammasome assembly-mediated IL-1β secretion. The calcium-sensing receptor (CaSR) and calcium signaling play crucial roles in the assembly of the NLRP3 inflammasome. WB and immunofluorescence results showed that ERβ activation reduced intracellular CaSR expression and calcium signaling in colonic macrophages. Combination with CaSR overexpression plasmid reversed the suppressive effect of ERβ activation on NLRP3 inflammasome assembly, and counteracting the downregulation of IL-1β secretion. Conclusion: Our research uncovers that the anti-colitis effect of ERβ activation is accomplished through the reduction of IL-1β levels in colonic tissue, achieved by specifically decreasing CaSR expression in macrophages to lower intracellular calcium levels and inhibit NLRP3 inflammasome assembly-mediated IL-1β production.